Developing a building fire information management system based on 3D object visualization - Jung, Suhyun; Cha, Hee Sung; Jiang, Shaohua (Applied Sciences (Switzerland), 2020)
In a building fire disaster, a variety of information on hazardous factors is crucial for emergency responders, facility managers, and rescue teams. Inadequate information management limits the accuracy and speed of fire rescue activities. Furthermore, a poor decision-making process, which is solely dependent on the experiences of emergency responders, negatively affects the fire response activities. Building information modeling (BIM) enables the sharing of locations of critical elements and key information necessary for effective decision-making on disaster prevention. However, it is non-trivial to integrate and link the relevant information generated during the life cycle of the building. In particular, the information requirements for building fires should be retrieved in the BIM software because most of them have spatial characteristics. This paper proposes a prototype system for a building's fire information management using three-dimensional (3D) visualization by deriving the relevant information required for mitigating building fire disasters. The proposed system (i.e., Building Fire Information Management System (BFIMS) automatically provides reliable fire-related information through a computerized and systematic approach in conjunction with a BIM tool. It enables emergency responders to intuitively identify the location data of indoor facilities with its pertinent information based on 3D objects. Through scenario-based applications, the system has effectively demonstrated that it has contributed to an improvement of rapid access to relevant information.
Keywords: Building information modeling (BIM); Facility management; Fire disaster